Rare presentation of AICA syndrome. (23rd January 2018) - Shabbir, Syed H; Nadeem, Faryal; Labovitz, Daniel
Abstract : We report a rare presentation of an anterior inferior cerebellar artery (AICA) infarct in a 74-year-old woman with acute-onset nausea, vomiting, vertigo and gait instability long before the full onset of symptoms and a negative MRI on admission. Over the next several days the patient developed left facial weakness, numbness, hypoacusis, and limb and gait ataxia, and was found to have acute infarcts of the left pons and cerebellar peduncle consistent with an AICA syndrome. We discuss this rare stepwise presentation in AICA syndrome and possible underlying pathophysiology. Such patients at risk for cerebrovascular disease should undergo a careful history, exam and follow-up, even with negative MRI findings, as their symptoms may precede a serious vascular event.